27 The association of frailty and coronary artery disease burden in older patients with non-st elevation acute coronary syndrome. (27th November 2017) - Gu, Sophie Zhaotao; Batty, Jonathan; Jordan, Rebecca; Veerasamy, Murugapathy; Sinclair, Hannah; Bagnall, Alan; Das, Rajiv; Spyridopoulos, Ioakim; Egred, Mohaned; Zaman, Azfar; Purcell, Ian; Edwards, Richard; et al.
Abstract : Introduction: Frailty is common in older patients who present with Acute Coronary Syndrome (ACS). However, its association with coronary disease complexity measured by Syntax and British Cardiovascular Intervention Society jeopardy score (BCIS JS) is not known. Methods: 276 patients ≥75 years of age, admitted for invasive management of Non-ST Elevation ACS (NSTEACS), were enrolled into a 2 centre prospective observational study (ICON1 study-NCT01933581 ). Frailty was assessed using the Fried criteria (score 0 robust, 1 or 2 pre-frail and ≥3 is frail). Syntax 1.0 calculator, BCIS algorithm and Global Registry of Acute Coronary Events (GRACE) 2.0 calculator were used to calculate scores. Procedure complication includes dissection, distal embolization, abrupt closure, thrombus, perforation and loss of side branch evaluated at Newcastle angiographic core lab. Results: Frail patients tend to have higher GRACE 2.0 scores (124.0±13.7 vs 131.3±19.7 vs 136.0±19.5, p=0.008). With increasing frailty, there was a non-significant increase in the proportion with SYNTAX score greater than 22 (20.8% vs 27.5% vs 31.5%, p=0.436) and BCIS JS ≥6 (56.0% vs 61.6% vs 64.1%, p=0.651). Frail patients were more likely to have moderate to severe calcification (34% vs 44.8% vs 62.0%, p=0.005). Overall procedure complication rate is low at 4.6%, with no difference among frailty groups (2.3% vs 4.5% vs 6.3%, p=0.76). Conclusions: Frail older patients have higher GRACE score and more severe calcification in the coronary arteries. However, the complexity of coronary disease is not significantly different in this patient group.